Positive Psychosocial Strengths: a Potential Intervention Framework for Adolescents’ Career Development - Αργυροπούλου, Κατερίνα; Χαροκοπάκη, Αργυρώ; Νανόπουλος, Παναγιώτης; Τερζάκη, Μαρία (Education Sciences, 2022)
Adolescents' careers are no longer linear. In modern times, career success is based, besides to technical knowledge on additional positive characteristics or strengths that adolescents should develop in order to meet the needs of the labor market. This article presents the relationship between positive psychosocial strengths (future orientation, resilience, gratitude and psychological well-being) and career research. The results showed that positive psychosocial strengths are a predictor of adolescents' subjective view of their future and their subjective sense of well-being. The results are discussed in the context of career counseling. Implications for counseling interventions are also discussed.